Heart 3D: echocardiographic and anatomical features of the tricuspid valve in a heterogeneous population with severe regurgitation—implications for edge-to-edge procedure suitability - Sobieraj, Jan; Rdzanek, Adam; Kapłon-Cieślicka, Agnieszka; Huczek, Zenon; Tomaniak, Mariusz; Ostrowska, Ewa; Piasecki, Adam; Pędzich, Ewa; Scisło, Piotr (Frontiers in Cardiovascular Medicine, 2025)
AimTo assess the incremental value of real-time three-dimensional (3D) transesophageal echocardiography (TEE) in visualizing tricuspid valve (TV) anatomy for procedural planning and guidance of transcatheter edge-to-edge repair (TEER) in cases of severe tricuspid regurgitation (TR).Materials and methodsAn observational study was conducted on 54 patients with severe TR. The visualization of the TV leaflets during systole was graded semiquantitatively using predefined criteria: 0 points—no visible leaflet border or tissue; 1.25—border only; 2—border and <50% tissue; 3—border and >50% tissue. Each of the three leaflets was evaluated independently in both two-dimensional (2D) and 3D TEE, with a maximum cumulative score of 9. Two thresholds were established: ≥4.5 points as the primary endpoint for adequate visualization for TEER planning and ≥6 points as the secondary endpoint indicating sufficient quality for a detailed morphological assessment.ResultsIn 3D TEE, 77.8% of patients achieved the primary endpoint, and 68.5% reached the secondary threshold. In comparison, 2D TEE enabled 74.1% and 42.6% of patients to meet these respective thresholds. Although the difference in achieving the primary endpoint was not statistically significant (p = 0.82), 3D TEE significantly outperformed 2D TEE in enabling a detailed morphological evaluation (p = 0.012). No significant differences were noted in the visualization quality of the anterior vs. septal leaflets with 3D TEE (67.4% vs. 65.4%, p = 0.800). For the posterior leaflet, 3D TEE provided superior visualization compared with the 2D TEE (p = 0.0008), while still supporting procedural suitability in a comparable proportion of patients (85.4% vs. 89.8%, p = 0.400). Acoustic shadowing from the interatrial septum and aortic root accounted for 92% of inadequate visualizations.ConclusionIn this observational study, real-time 3D TEE proved feasible for assessing tricuspid valve anatomy and visualization quality in patients with severe TR who were considered for TEER. Compared with 2D TEE, 3D TEE offered an improved visualization of the posterior leaflet and provided adequate image quality for procedural planning in most patients. Moreover, a statistically significant advantage was observed for 3D TEE over 2D TEE in providing image quality sufficient for a detailed morphological evaluation.